2017
DOI: 10.1007/s11427-017-9170-3
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing machinery in plant organelles

Abstract: RNA editing is a type of post-transcriptional modification that includes nucleotide insertion/deletion or conversion. Different categories of RNA editing have been widely observed in distinct RNAs from divergent organisms. In flowering plants, RNA editing usually alters cytidine to uridine in plastids and mitochondria, playing important roles in various plant developmental processes, including organelle biogenesis, adaptation to environmental changes, and signal transduction. Numerous studies have demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 56 publications
4
79
0
Order By: Relevance
“…RNA analyses have shown that RNA editing (mainly in the form of C-to-U base conversions) is highly widespread within the chloroplasts of land plants. During this process, numerous C-to-U conversions alter the coding sequences of chloroplast mRNAs, regulate RNA secondary structures that influences the splicing and/or stability of RNAs, or generate translational start sites (AUG) [ 47 , 48 ]. All of these RNA metabolic events depend on many nucleus-encoded proteins, most of which likely arose during coevolution between the host and endosymbiont.…”
Section: The Characteristics Of Chloroplast Gene Expressionmentioning
confidence: 99%
“…RNA analyses have shown that RNA editing (mainly in the form of C-to-U base conversions) is highly widespread within the chloroplasts of land plants. During this process, numerous C-to-U conversions alter the coding sequences of chloroplast mRNAs, regulate RNA secondary structures that influences the splicing and/or stability of RNAs, or generate translational start sites (AUG) [ 47 , 48 ]. All of these RNA metabolic events depend on many nucleus-encoded proteins, most of which likely arose during coevolution between the host and endosymbiont.…”
Section: The Characteristics Of Chloroplast Gene Expressionmentioning
confidence: 99%
“…In higher plants, RNA editing usually occurs in plastids and mitochondria and plays important roles in organelle biogenesis, environmental adaptation and development. Yan et al discuss the divergent roles of the plant RNA editing factors such as pentatricopeptide repeat (PPR) proteins, multiple organelle RNA editing factors (MORF, also known as RIP), organelle RNA recognition motif (ORRM) containing proteins, protoporphyrinogen IX oxidase 1 (PPO1) and organelle zinc finger 1 (OZ1) (Yan et al, 2018).…”
Section: Non-coding Rnas: the Long And The Short Of Themmentioning
confidence: 99%
“…Numerous studies have demonstrated that RNA editing plays an important role in various plant fundamental processes, such as organelle biogenesis, adaptation to environmental changes, and signal transduction [8][9][10]. A number of factors are involved in plant RNA editing, and considered to interact with one another to form a large protein complex, termed as editsome, PLS subfamily members of pentatrico peptide repeat (PPR) proteins function in site recognition of the target C, multiple organelle RNA editing factors (MORF) family members are components of the RNA editosome and also required for RNA editing at multiple editing sites in plants [11,12]. Almost all the PPR proteins are localized in either chloroplasts or mitochondria where those proteins participate in different facets of RNA metabolism such as RNA splicing, RNA stability, and translational initiation [13].…”
Section: Introductionmentioning
confidence: 99%